Penggunaan Bahan Berbahaya Pada Produk Kosmetik Yang Beredar di Pasaran Menurut Perspektif Al-Islam dan Kemuhammadiyahan - Khasanah, Nur; Yusron, Miftakhul; Oman Fathurohman SW (An-Najat, 2025)
The tendency to use cosmetics in society makes cosmetic manufacturers compete to make their cosmetic products attractive and favored by buyers. Sometimes without paying attention to safety so that it can cause harm. This research aims to find out the use of hazardous materials in cosmetic products on the market according to the perspective of Al-Islam and Kemuhammadiyahan. From the results of this study, it is found that there are still many cosmetic products on the market that use prohibited or dangerous ingredients. This means that there are still many producers who have not been able to apply BPOM regulations, Islamic values and Muhammadiyah principles in practice in the pharmaceutical industry. Because from the perspective of Islam and Muhammadiyah, making cosmetics with hazardous ingredients can bring harm which is prohibited and contradictory.